ROSCOEA MEGALANTHA (ZINGIBERACEAE), A NEW SPECIES FROM EASTERN BHUTAN AND INDIA - Yoshida, T.; Yangzom, R.; Newman, M. F. (Edinburgh Journal of Botany, 2017)
A new species of Roscoea is described and illustrated. Roscoea megalantha Tosh.Yoshida & R.Yangzom occurs in the Eastern Zone of Bhutan and neighbouring Arunachal Pradesh in India. A distribution map and an IUCN conservation assessment are given. A key to the three species of Roscoea found in Bhutan is provided.